(untitled) (Research, Society and Development, 2021)
The study of occlusion, besides being one of the most controversial areas of dentistry, also brings fear to many professionals regarding its concepts and correct application and correlation. However, the correct analysis of the stomatognathic system and the patient’s occlusal relationship guarantees, despite everything, a safer rehabilitation for the patient and for the professional. The aim of this study was to analyze and display indices through a systematic review related to the contemporary teaching of dentistry and the preparation of professionals to diagnose and treat temporomandibular and occlusal conditions, including their dysfunctions. The review was carried out according to parameters of the Cochrane organization, through references included by searches in the Science Direct, PubMed, LILACS and Google Scholar databases, all in English. The research showed a great lack of knowledge on the part of students and professionals about the study of occlusion, evidencing a gap in didactics in this area that has dragged on for decades. This reality perpetuates the dissemination of concepts without a scientific basis, while some professionals are concerned, and try by themselves, to define parameters of diagnosis and treatment for patients covered by this coverage area.